Single-layer core-shell structure polishing abrasive for silicon carbide wafer polishing, polishing solution, preparation method and polishing method
By preparing single-layer core-shell structured polishing abrasives using electrostatic adsorption and cationic polyelectrolyte-assisted methods, the problems of abrasive dispersion stability and surface quality in silicon carbide wafer polishing were solved, achieving high-efficiency polishing results and low-cost industrial production.
Patent Information
- Application Number
- CN202511219500.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-12-12
AI Technical Summary
In existing silicon carbide wafer polishing technology, the particle size ratio, coating uniformity and dispersion stability of the abrasive are insufficient, resulting in problems such as agglomeration, scratches and insufficient polishing rate. Moreover, the existing composite abrasive preparation methods are complex and costly, making it difficult to meet industrialization requirements.
By employing electrostatic adsorption and cationic polyelectrolyte-assisted methods, a silica core with a particle size of 300nm-800nm is uniformly coated with an alumina layer of 25nm-150nm thickness, forming a single-layer core-shell structure polishing abrasive. The combination of the high hardness of the alumina shell and the elastic deformation of the silica core ensures polishing efficiency and surface quality.
It achieves efficient silicon carbide wafer polishing, obtaining sub-nanometer-level surface roughness and low scratch density, reducing production costs, and is suitable for mass production and precision machining of high-end power devices.
Smart Images

Figure CN121108880A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical mechanical polishing technology, and more particularly to a single-layer core-shell structure polishing abrasive, polishing fluid, preparation method, and polishing method for polishing silicon carbide wafers. Background Technology
[0002] In semiconductor manufacturing, chemical mechanical polishing (CMP) is a key process for achieving global planarization of the wafer surface. In silicon carbide (SiC) substrate manufacturing, the final polishing process is crucial for achieving sub-nanometer-level surface flatness and reducing defect density, while the abrasive in the polishing slurry is the core factor affecting the polishing effect.
[0003] Currently, commonly used abrasives include alumina and silica. Alumina has high hardness and a fast polishing rate, but it is prone to scratches and other defects on the polished surface. Silica abrasives can achieve better surface quality, but the polishing rate is relatively low. To balance efficiency and surface quality, core-shell structured abrasives have been proposed, such as alumina core / silica shell (for rough polishing). While this reduces scratches, it sacrifices polishing efficiency and requires ball milling, resulting in higher energy consumption.
[0004] However, these methods often fail to optimize particle size distribution, coating uniformity, and dispersion stability for SiC polishing, resulting in problems such as agglomeration, scratches, and insufficient abrasive rates in high-precision machining. Furthermore, existing composite abrasive preparation methods suffer from complex processes, high costs, and poor composite effects, making them unsuitable for industrial production. Therefore, developing a simple, low-cost, and high-performance CMP (chemical mechanical polishing) polishing slurry composite abrasive preparation method is of great significance. Summary of the Invention
[0005] The aforementioned methods for preparing composite abrasives suffer from technical problems such as complex operation, high cost, and poor dispersion and surface quality of composite particles. This invention provides a single-layer core-shell structure polishing abrasive, polishing fluid, and preparation and polishing methods for silicon carbide wafer polishing, characterized by a simple preparation process, high coating uniformity, and excellent dispersion stability. It is particularly suitable for the final polishing of silicon carbide wafers. This invention primarily utilizes electrostatic adsorption and cationic polyelectrolyte assistance to uniformly coat a 25nm-150nm thick alumina layer onto the surface of a 300nm-800nm diameter silica core, forming a single-layer structure. The high hardness of the alumina shell ensures a high material removal rate, while the elastic deformation of the silica core absorbs polishing pressure, reducing surface roughness to 0.1nm-0.2nm. This ensures the synergistic effect of the abrasive hardness gradient and chemical activity, effectively reducing agglomeration rate, thereby achieving sub-nanometer-level surface roughness while maintaining a high removal rate. Furthermore, the polishing fluid of this invention possesses both environmental and safety characteristics, making it promising for large-scale application.
[0006] The technical means employed in this invention are as follows: A single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers, wherein the single-layer core-shell structured polishing abrasive has a silicon dioxide core and an aluminum oxide shell, with the shell covering the outside of the core, and the single-layer coating is achieved by electrostatic adsorption assisted by cationic polyelectrolytes.
[0007] Furthermore, the silicon dioxide has a particle size of 300-800 nm, the alumina has a particle size of 10-150 nm, the particle size ratio of the core to the shell is 2:1-10:1, and the coating thickness is controlled at 25-150 nm.
[0008] The present invention also provides a polishing fluid comprising the above-mentioned single-layer core-shell structure polishing abrasive, oxidant, dispersant and deionized water.
[0009] Furthermore, the polishing fluid comprises the following raw materials by mass fraction: 3-15 parts of single-layer core-shell structure polishing abrasive, 0.2-8 parts of oxidant, 0.1-8 parts of dispersant, and the balance being deionized water, with the sum of the above raw materials being 100 parts; the pH value of the polishing fluid is 8-11.
[0010] This invention also provides a method for preparing a single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers, comprising the following steps: Step 1: Prepare a 2wt%-4wt% alumina suspension and a 2wt%-4wt% silica suspension, adjust the pH of the alumina suspension and silica suspension to between 8 and 11, and then perform ultrasonic dispersion. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge for 10-30 minutes. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process multiple times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: The obtained positively charged alumina particles are redispersed in deionized water with a pH between 8 and 11. While stirring, the ultrasonically dispersed silica suspension is added until the mixture is homogeneous, resulting in a second suspension. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge for 10-30 minutes. Dry the resulting solid to obtain a single-layer core-shell structure polishing abrasive. Step 6: Dissolve 1-15 parts of single-layer core-shell structure polishing abrasive in 85-99 parts of deionized water, stir evenly to obtain a third suspension, and measure the zeta potential and particle size of the third suspension.
[0011] Furthermore, in step 1, the ultrasonic dispersion time is 15 min-30 min; In step 1, the purity of alumina in the alumina suspension is 99.9%-99.99%, and the purity of silica in the silica suspension is 99.9%-99.99%. In step 2, the cationic polyelectrolyte is one or more of polyacrylamide, polyethyleneimine, chitosan, and polydimethyldiallylammonium chloride; the stirring speed is 200 r / min-400 r / min, and the stirring time is 30 min-60 min.
[0012] Furthermore, in step 3, the speed of the high-speed centrifuge is 2000 r / min-4000 r / min; In step 4, the stirring time is 30-60 minutes; In step 5, the high-speed centrifuge speed is 2000-4000 r / min, the drying temperature is 80°-110°, and the drying time is 15 min-30 min.
[0013] The present invention also provides a method for preparing a polishing slurry, comprising the following steps: S1. Mix 0.1-10 parts of dispersant with 85-95 parts of deionized water to obtain a diluted dispersant solution; S2. Add 3-15 parts of single-layer core-shell structured polishing abrasive to the diluted dispersant solution and stir thoroughly for 10-30 minutes to obtain a well-dispersed core-shell structured abrasive suspension. S3. Add 1-20 parts of oxidant to the core-shell structure abrasive suspension and mix thoroughly for 20-40 minutes to obtain the core-shell structure abrasive polishing slurry.
[0014] Further, in S1, the dispersant is at least one of sodium hexametaphosphate and sodium polyacrylate; In S3, the oxidant is at least one of potassium permanganate, hydrogen peroxide, and ammonium persulfate.
[0015] The present invention also provides a polishing method for performing final polishing on a silicon carbide wafer using the above-mentioned polishing slurry, comprising the following steps: Step 1: Stir the prepared polishing liquid evenly, set the polishing pressure to 2psi-8psi, and the polishing disc speed to 50rpm-300rpm; Step 2: Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 150ml / min-500ml / min. After wetting, start the equipment and polish continuously for 30min-90min. Step 3: After polishing, remove the silicon carbide wafer and ultrasonically vibrate it for 5-20 minutes to remove the abrasive adhering to the silicon carbide wafer, obtaining polished silicon carbide. Then, test the roughness and removal rate after polishing.
[0016] Compared with the prior art, the present invention has the following advantages: 1. The core-shell structured abrasive prepared by electrostatic adsorption and cationic polyelectrolyte combines the advantages of alumina particles and silica particles, achieving both high polishing rate and excellent surface quality, effectively solving the defects of single abrasives.
[0017] 2. The preparation process of this invention is simple, convenient to operate, and requires conventional equipment, which helps to reduce production costs and is suitable for large-scale industrial production. Furthermore, the preparation conditions of the core-shell structure are mild and easy to control, and the prepared single-layer core-shell abrasive exhibits stable performance and has good application prospects in CMP polishing slurries.
[0018] 3. The core-shell structure polishing abrasive prepared by this invention has a lower hardness than the outer shell abrasive, and has high dispersibility and low agglomeration rate (≤5%). In the final polishing process of SiC wafers, a surface roughness of Ra≤0.15nm can be obtained, while maintaining a material removal rate of ≥1500nm / h, significantly reducing scratch density, and is suitable for mass fine processing of high-end power device substrates.
[0019] Based on the above reasons, this invention can be widely applied in fields such as final polishing of silicon carbide wafers. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The images show a comparison of the surface roughness of polished silicon carbide in various embodiments and comparative examples of the present invention.
[0022] Figure 2 This is a comparison chart of the removal rates of silicon carbide after polishing in various embodiments and comparative examples of the present invention. Detailed Implementation
[0023] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0026] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values of the components and steps described in these embodiments do not limit the scope of the invention. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following figures denote similar items; therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0027] This invention provides a single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers. The single-layer core-shell structured polishing abrasive uses silicon dioxide with a particle size of 300-800 nm as the core and alumina with a particle size of 10-150 nm as the outer shell. The outer shell covers the outside of the core, and the particle size ratio of the core to the outer shell is 2:1-10:1. The single-layer coating is achieved by electrostatic adsorption assisted by cationic polyelectrolyte, and the coating thickness is controlled at 25-150 nm.
[0028] The present invention also provides a polishing liquid, comprising, by weight: 3-15 parts of single-layer core-shell structure polishing abrasive, 0.2-8 parts of oxidant, 0.1-8 parts of dispersant, and the balance being deionized water, wherein the sum of the above raw materials is 100 parts, and the pH value of the polishing liquid is adjusted to 8-11.
[0029] The core-shell structured abrasive prepared by this invention has a lower hardness than the outer shell abrasive, and exhibits high dispersibility and low agglomeration rate (≤5%). During the final polishing process of SiC wafers, it can achieve a surface roughness of Ra≤0.15nm while maintaining a material removal rate of ≥1500nm / h, significantly reducing scratch density, and is suitable for mass production and finishing of high-end power device substrates.
[0030] This invention also provides a method for preparing a single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers, comprising the following steps: Step 1: Prepare a 2wt%-4wt% alumina suspension and a 2wt%-4wt% silica suspension, adjust the pH of the alumina suspension and silica suspension to between 8 and 11, and then perform ultrasonic dispersion. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir and vibrate thoroughly to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge for 10-30 minutes. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process multiple times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: The obtained positively charged alumina particles are redispersed in deionized water with a pH between 8 and 11. While stirring, the ultrasonically dispersed silica suspension is added until the mixture is homogeneous, resulting in a second suspension. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge for 10-30 minutes. Dry the resulting solid to obtain the final single-layer core-shell structure polishing abrasive. Step 6: Dissolve 1-15 parts of single-layer core-shell structure polishing abrasive in 85-99 parts of deionized water, stir evenly to obtain a third suspension, and measure the zeta potential and particle size of the third suspension.
[0031] In the embodiments of the present invention, the particle size of alumina in step 1 is 10nm-150nm, and the particle size of silica is 300nm-800nm. The large-size silica core provides an elastic buffer layer to absorb polishing pressure, and the thickness of the alumina shell needs to cover the core without falling off. If it is too thin, the hardness will be insufficient, and if it is too thick, it will easily agglomerate. Therefore, the thickness of a single coating layer should be controlled between 25nm-150nm to balance the removal rate and surface quality. In order to ensure that the hardness of the outer shell alumina dominates the removal effect and the core silica dominates the protection effect, the particle size ratio of the core to the shell is preferably 2:1-10:1 to synergistically improve the removal rate and surface quality.
[0032] In the embodiments of the present invention, the purity of alumina in the alumina suspension in step 1 is 99.9%-99.99%, and the purity of silica in the silica suspension is 99.9%-99.99%.
[0033] In the embodiments of the present invention, in step 1, if the solid content is too low (<2wt%), the particle collision probability is low and the coating efficiency is poor; if it is too high (>6wt%), agglomeration is easily initiated by van der Waals forces. Therefore, 2wt%-4wt% ensures sufficient particle density while maintaining dispersion stability through electrostatic repulsion. Alkaline conditions cause the alumina surface to become negatively charged, preparing it for electrostatic adsorption. Ultrasonic dispersion for 15-30 minutes ensures uniform dispersion of alumina particles in the alkaline alumina suspension, providing a good foundation for subsequent surface treatment.
[0034] In embodiments of the present invention, in step 2, stirring and agitation are used to ensure that an appropriate amount of cationic polyelectrolyte is fully adsorbed onto the surface of the alumina particles, ensuring that all alumina particle surfaces are covered with polyelectrolyte, making the alumina particle surfaces positively charged. Simultaneously, excessive polyelectrolyte is avoided from remaining in the solution, which could shield the positive charge on the alumina surface and reduce the adsorption force on silica. Therefore, the concentration of cationic polyelectrolyte is preferably 0.05wt%-2wt% to prevent particle aggregation and ensure more stable subsequent binding with negatively charged silica. Furthermore, low stirring speed and short time will prevent the cationic polyelectrolyte from being fully adsorbed; therefore, the stirring speed is preferably 200r / min-400r / min, and the time is preferably 30min-60min.
[0035] In the embodiments of the present invention, in step 2, the cationic polyelectrolyte is one or more of polyacrylamide, polyethyleneimine, chitosan, and polydimethyldiallyl ammonium chloride.
[0036] In this embodiment of the invention, in step 3, the speed of the high-speed centrifuge is preferably 2000 r / min-4000 r / min. The high speed ensures the separation effect and guarantees the purity of the subsequent composite. Repeating the process three times can thoroughly remove free polyelectrolytes and avoid impurities interfering with the coating. Through centrifugal separation and repeated dissolution centrifugation, cationic polyelectrolytes not adsorbed on the surface of alumina particles can be removed, improving the purity of the alumina particles and ensuring the subsequent composite effect with the silica suspension.
[0037] In the embodiments of the present invention, in step 4, there is electrostatic attraction between the positively charged alumina particles and the negatively charged silica particles, which can achieve good composite under stirring conditions. Adding silica sol and continuing to stir for a period of time can make the abrasive composite more complete; the stirring time is preferably 30-60 minutes to ensure uniform single-layer coating and avoid multi-layer or agglomeration.
[0038] In the embodiments of the present invention, in step 5, the speed of the high-speed centrifuge is preferably 2000-4000 r / min, the drying temperature is 80°-110°, and the drying time is 15min-30min, so as to prevent the core-shell structure from being damaged by high temperature and long-term drying, and to preserve the abrasive performance.
[0039] This invention also discloses a method for preparing a single-layer core-shell structured abrasive polishing slurry for polishing silicon carbide wafers, comprising the following steps: S1. Mix 0.1-10 parts of dispersant with 85-95 parts of deionized water to obtain a diluted dispersant solution, forming a stable medium; S2. Add 3-15 parts of single-layer core-shell structure polishing abrasive to the diluted dispersant solution and stir thoroughly for 10-30 minutes to ensure that the abrasive is fully dispersed and to obtain a well-dispersed core-shell structure abrasive suspension. S3. Finally, to prevent the oxidant from reacting prematurely, add 1-20 parts of oxidant to the core-shell abrasive suspension and mix thoroughly for 20-40 minutes to obtain the core-shell abrasive polishing slurry.
[0040] In embodiments of the present invention, the dispersant in S1 includes one or more of sodium hexametaphosphate, sodium polyacrylate, etc.
[0041] In embodiments of the present invention, the oxidant in S3 includes one or more of potassium permanganate, hydrogen peroxide, and ammonium persulfate.
[0042] In a specific embodiment, the present invention also provides a polishing method, which uses the above-mentioned polishing slurry to perform final polishing on silicon carbide wafers, and continuously polishes for 30 min to 90 min at a pressure of 2 psi-8 psi, a polishing disc rotation speed of 50 rpm-300 rpm, and a polishing slurry flow rate of 150 mL / min-500 mL / min.
[0043] Polishing methods specifically include: Step 1: Stir the prepared polishing slurry evenly. Set the polishing pressure to 2psi-8psi, as low pressure reduces surface damage and high pressure increases the removal rate. Set the polishing disc speed to 50rpm-300rpm, as low speed reduces uneven abrasive distribution caused by centrifugal force, ensuring uniform coverage of the polishing slurry and reducing scratch density. Step 2: Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it at a flow rate of 150ml / min-500ml / min. The high flow rate will remove debris in time and prevent secondary scratches. After wetting, start the equipment and polish continuously for 30min-90min. Step 3: After polishing, remove the silicon carbide wafer and ultrasonically vibrate it for 5-20 minutes to remove the abrasive adhering to the wafer, obtaining polished silicon carbide. Then, test the roughness and removal rate after polishing.
[0044] Specifically, in the embodiments of the present invention, a nanoparticle size and zeta potential analyzer (ZS90) is used to detect the dispersibility of the single-layer core-shell structure suspension; a 3D surface energy optical profilometer is used to detect the surface quality of the polished silicon carbide wafer; and the removal rate after polishing is calculated by weighing method.
[0045] The following are specific examples: Example 1 The fabrication scheme for the single-layer core-shell structure in this embodiment is as follows: Step 1: Prepare a suspension of 2wt%-4wt% alumina with a particle size of 10nm and a suspension of 2wt%-4wt% silica with a particle size of 300nm. Adjust the pH of the alumina suspension and silica suspension to 10 and then perform ultrasonic dispersion for 15min. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly at 200 r / min for 30 min to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge at 2000 r / min for 15 min. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process three times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: The obtained positively charged alumina particles are redispersed in deionized water with pH=10. While stirring, the ultrasonically dispersed silica suspension is added and stirred for 30 minutes. After stirring evenly, a second suspension is obtained. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge at 2000 r / min for 20 min to obtain a solid. Dry the solid at 80°C for 15 min to obtain the final single-layer core-shell structure polishing abrasive. Step 6: Dissolve 5 parts of single-layer core-shell structure polishing abrasive in 95 parts of deionized water, stir evenly to obtain the third suspension. The zeta potential of the third suspension was measured to be -47.86mV and the particle size was 537nm.
[0046] The preparation method of the core-shell structure abrasive polishing slurry in this embodiment includes the following steps: 1) Mix 0.5 parts of dispersant with 91.5 parts of deionized water to obtain a diluted dispersant solution; 2) Add 5 parts of single-layer core-shell structured polishing abrasive to a diluted dispersant solution and stir thoroughly for 20 minutes to obtain a well-dispersed core-shell structured abrasive suspension; 3) Add 3 parts of oxidant to the core-shell structure abrasive suspension and mix thoroughly for 30 minutes to obtain a final core-shell structure abrasive polishing slurry of 100 parts.
[0047] The polishing method of this embodiment includes the following steps: (1) Place the prepared polishing liquid in the tank, stir it evenly, set the polishing pressure to 4 psi and the polishing disc speed to 50 rpm; (2) Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 150 ml / min. After wetting, start the equipment and polish continuously for 60 min. (3) After polishing, the silicon carbide wafer was removed and ultrasonically vibrated for 10 minutes to obtain polished silicon carbide. The roughness after polishing was measured to be 0.11 nm and the removal rate was 1923 nm / h.
[0048] Example 2 The fabrication scheme for the single-layer core-shell structure in this embodiment is as follows: Step 1: Prepare a suspension of 2wt%-4wt% alumina with a particle size of 150nm and a suspension of 2wt%-4wt% silica with a particle size of 800nm. Adjust the pH of the alumina suspension and silica suspension to 10 and then perform ultrasonic dispersion for 15min. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly at 200 r / min for 30 min to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge at 4000 r / min for 15 min. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process three times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: The obtained positively charged alumina particles are redispersed in deionized water with pH=10. While stirring, the ultrasonically dispersed silica suspension is added and stirred for 60 minutes. After stirring evenly, a second suspension is obtained. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge at 4000 r / min for 20 min to obtain a solid. Dry the solid at 110° for 30 min to obtain the final single-layer core-shell structure polishing abrasive.
[0049] The preparation method of the core-shell structure abrasive polishing slurry in this embodiment includes the following steps: 1) Mix 5 parts of dispersant with 80 parts of deionized water to obtain a diluted dispersant solution; 2) Add 10 parts of single-layer core-shell structured polishing abrasive to a diluted dispersant solution and stir thoroughly for 20 minutes to obtain a well-dispersed core-shell structured abrasive suspension. 3) Add 5 parts of oxidant to the core-shell structure abrasive suspension and mix thoroughly for 30 minutes to obtain a final core-shell structure abrasive polishing slurry of 100 parts.
[0050] The polishing method of this embodiment includes the following steps: (1) Place the prepared polishing liquid in the tank, stir evenly, set the polishing pressure to 4psi and the polishing disc speed to 300rpm; (2) Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 500 ml / min. After wetting, start the equipment and polish continuously for 60 min. (3) After polishing, the silicon carbide wafer was removed and ultrasonically vibrated for 10 minutes to obtain polished silicon carbide. The roughness after polishing was measured to be 0.16 nm and the removal rate was 1865 nm / h.
[0051] Example 3 The fabrication scheme for the single-layer core-shell structure in this embodiment is as follows: Step 1: Prepare a suspension of 2wt%-4wt% alumina with a particle size of 50nm and a suspension of 2wt%-4wt% silica with a particle size of 550nm. Adjust the pH of the alumina suspension and silica suspension to 10 and then perform ultrasonic dispersion for 15min. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly at 300 r / min for 45 min to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge at 3000 r / min for 15 min. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process three times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: The obtained positively charged alumina particles are redispersed in deionized water with pH=10. While stirring, the ultrasonically dispersed silica suspension is added and stirred for 45 minutes. After stirring evenly, a second suspension is obtained. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge at 3000 r / min for 20 min to obtain a solid. Dry the solid at 95° for 25 min to obtain the final single-layer core-shell structure polishing abrasive.
[0052] The preparation method of the core-shell structure abrasive polishing slurry in this embodiment includes the following steps: 1) Mix 10 parts of dispersant with 75 parts of deionized water to obtain a diluted dispersant solution; 2) Add 15 parts of single-layer core-shell structured polishing abrasive to a diluted dispersant solution and stir thoroughly for 20 minutes to obtain a well-dispersed core-shell structured abrasive suspension. 3) Add 10 parts of oxidant to the core-shell structure abrasive suspension and mix thoroughly for 30 minutes to obtain a final core-shell structure abrasive polishing slurry of 100 parts.
[0053] The polishing method of this embodiment includes the following steps: (1) Place the prepared polishing liquid in the tank, stir it evenly, set the polishing pressure to 4psi and the polishing disc speed to 150rpm; (2) Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 250 ml / min. After wetting, start the equipment and polish continuously for 60 min. (3) After polishing, the silicon carbide wafer was removed and ultrasonically vibrated for 10 minutes to obtain polished silicon carbide. The roughness after polishing was measured to be 0.14 nm and the removal rate was 1736 nm / h.
[0054] Comparative Example 1 The preparation scheme of this comparative abrasive suspension is as follows: Step 1: Prepare an alumina suspension with a particle size of 50 nm at a concentration of 2 wt%-4 wt%, adjust the pH of the alumina suspension to 10, and ultrasonically disperse the alumina suspension for 15 min. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly at 200 r / min for 30 min to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge at 2000 r / min for 15 min. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process three times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: Redisperse the obtained positively charged alumina particles in deionized water with pH=10 and stir for 30 min; Step 5: Place the well-stirred suspension into a centrifuge and centrifuge at 2000 r / min for 20 min to obtain a solid. Dry the solid at 80°C for 15 min to obtain the final alumina abrasive. Step 6: Dissolve 5 parts of the final alumina abrasive in 95 parts of deionized water, stir evenly to obtain a suspension, and measure the zeta potential of the suspension as 44.82 mV and the particle size as 56 nm.
[0055] The preparation method of this comparative polishing slurry includes the following steps: 1) Mix 0.5 parts of dispersant with 91.5 parts of deionized water to obtain a diluted dispersant solution; 2) Add 5 parts of alumina abrasive to the diluted dispersant solution and stir thoroughly for 20 minutes to obtain a well-dispersed abrasive suspension; 3) Add 3 parts of oxidant to the abrasive suspension and mix thoroughly for 30 minutes to obtain a final polishing solution of 100 parts.
[0056] The polishing method in this comparative example includes the following steps: (1) Place the prepared polishing liquid in the tank, stir it evenly, set the polishing pressure to 4 psi and the polishing disc speed to 50 rpm; (2) Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 150 mL / min. After wetting, start the equipment and polish continuously for 60 min. (3) After polishing, the silicon carbide wafer was removed and ultrasonically vibrated for 10 minutes to obtain polished silicon carbide. The roughness after polishing was measured to be 0.15 nm and the removal rate was 1265 nm / h.
[0057] Comparative Example 2 The preparation scheme of this comparative abrasive suspension is as follows: Five parts of 300nm silica abrasive were dissolved in 95 parts of deionized water and stirred evenly to obtain a suspension. The zeta potential of the suspension was measured to be -41.24mV and the particle size was 369nm.
[0058] The preparation method of this comparative polishing slurry includes the following steps: 1) Mix 0.5 parts of dispersant with 91.5 parts of deionized water to obtain a diluted dispersant solution; 2) Add 5 parts of silica abrasive to the diluted dispersant solution and stir thoroughly for 20 minutes to obtain a well-dispersed abrasive suspension; 3) Add 3 parts of oxidant to the abrasive suspension and mix thoroughly for 30 minutes to obtain a final polishing solution of 100 parts.
[0059] The polishing method in this comparative example includes the following steps: (1) Place the prepared polishing liquid in the tank, stir it evenly, set the polishing pressure to 4 psi and the polishing disc speed to 50 rpm; (2) Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 150 mL / min. After wetting, start the equipment and polish continuously for 60 min. (3) After polishing, the silicon carbide wafer was removed and ultrasonically vibrated for 10 minutes to obtain polished silicon carbide. The roughness after polishing was measured to be 0.18 nm and the removal rate was 1381 nm / h.
[0060] Table 1 shows a comparison of the zeta potential and particle size D50 of the abrasive suspensions in Example 1 and the comparative examples.
[0061] Table 1. Comparison of zeta potential and particle size D50 of abrasive suspensions in Example 1 and various comparative examples.
[0062] By comparing the zeta potential and particle size results of Example 1 and the comparative example, it is demonstrated that the alumina abrasive successfully encapsulates silicon dioxide, successfully constructing a single-layer core-shell structure.
[0063] By comparing the results of the above embodiments with those of the comparative examples, it is demonstrated that the removal rate of the embodiments of the present invention is significantly better than that of the single abrasive alumina and silicon dioxide polishing slurry in the comparative examples. Furthermore, the comparison of Example 1 and the comparative examples demonstrates that the surface quality of silicon carbide wafers polished with core-shell composite abrasives is improved.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers, characterized in that, The single-layer core-shell structured polishing abrasive uses silicon dioxide as the core and aluminum oxide as the outer shell, with the outer shell covering the outside of the core. The single-layer coating is achieved through electrostatic adsorption assisted by cationic polyelectrolytes.
2. The single-layer core-shell structure polishing abrasive for polishing silicon carbide wafers according to claim 1, characterized in that, The silicon dioxide has a particle size of 300-800nm, the alumina has a particle size of 10-150nm, the particle size ratio of the core to the shell is 2:1-10:1, and the coating thickness is controlled at 25-150nm.
3. A polishing liquid, characterized in that, It includes the single-layer core-shell structure polishing abrasive, oxidant, dispersant and deionized water as described in claim 1 or 2.
4. The polishing slurry according to claim 3, characterized in that, The polishing solution comprises the following raw materials by mass fraction: 3-15 parts of single-layer core-shell structure polishing abrasive, 0.2-8 parts of oxidant, 0.1-8 parts of dispersant, and the balance being deionized water, with the sum of the above raw materials being 100 parts; the pH value of the polishing solution is 8-11.
5. A method for preparing a single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers as described in claim 1 or 2, characterized in that, Includes the following steps: Step 1: Prepare a 2wt%-4wt% alumina suspension and a 2wt%-4wt% silica suspension, adjust the pH of the alumina suspension and silica suspension to between 8 and 11, and then perform ultrasonic dispersion. Step 2: Add 0.05%-2% of the cationic polyelectrolyte (by mass of the alumina suspension) to the ultrasonically dispersed alumina suspension, and stir thoroughly to obtain the first suspension; Step 3: Place the first suspension into a high-speed centrifuge and centrifuge for 10-30 minutes. Remove the supernatant to obtain a solid. Dissolve the solid again in deionized water and centrifuge. Repeat this process multiple times to wash away the unadsorbed cationic polyelectrolytes and obtain positively charged alumina particles. Step 4: Redisperse the obtained positively charged alumina particles in deionized water with a pH between 8 and 11, and add the ultrasonically dispersed silica suspension while stirring until the mixture is homogeneous to obtain a second suspension. Step 5: Place the well-stirred second suspension into a centrifuge and centrifuge for 10-30 minutes. Dry the resulting solid to obtain a single-layer core-shell structure polishing abrasive. Step 6: Dissolve 1-15 parts of single-layer core-shell structure polishing abrasive in 85-99 parts of deionized water, stir evenly to obtain a third suspension, and measure the zeta potential and particle size of the third suspension.
6. The method for preparing a single-layer core-shell structured polishing abrasive for silicon carbide wafer polishing according to claim 5, characterized in that, In step 1, the ultrasonic dispersion time is 15 min-30 min; In step 1, the purity of alumina in the alumina suspension is 99.9%-99.99%, and the purity of silica in the silica suspension is 99.9%-99.99%. In step 2, the cationic polyelectrolyte is one or more of polyacrylamide, polyethyleneimine, chitosan, and polydimethyldiallylammonium chloride; the stirring speed is 200 r / min-400 r / min, and the stirring time is 30 min-60 min.
7. The method for preparing a single-layer core-shell structured polishing abrasive for polishing silicon carbide wafers according to claim 5, characterized in that, In step 3, the speed of the high-speed centrifuge is 2000 r / min-4000 r / min; In step 4, the stirring time is 30-60 minutes; In step 5, the high-speed centrifuge speed is 2000-4000 r / min, the drying temperature is 80°-110°, and the drying time is 15 min-30 min.
8. A method for preparing the polishing slurry as described in claim 4, characterized in that, Includes the following steps: S1. Mix 0.1-10 parts of dispersant with 85-95 parts of deionized water to obtain a diluted dispersant solution; S2. Add 3-15 parts of single-layer core-shell structured polishing abrasive to the diluted dispersant solution and stir thoroughly for 10-30 minutes to obtain a well-dispersed core-shell structured abrasive suspension. S3. Add 1-20 parts of oxidant to the core-shell structure abrasive suspension and mix thoroughly for 20-40 minutes to obtain the core-shell structure abrasive polishing slurry.
9. The method for preparing the polishing slurry according to claim 8, characterized in that, In S1, the dispersant is at least one of sodium hexametaphosphate and sodium polyacrylate; In S3, the oxidant is at least one of potassium permanganate, hydrogen peroxide, and ammonium persulfate.
10. A polishing method, characterized in that, Final polishing of silicon carbide wafers using the polishing slurry as described in claim 4 includes the following steps: Step 1: Stir the prepared polishing liquid evenly, set the polishing pressure to 2psi-8psi, and the polishing disc speed to 50rpm-300rpm; Step 2: Use a peristaltic pump to draw up the well-stirred polishing liquid and inject it into the polishing disc at a flow rate of 150ml / min-500ml / min. After wetting, start the equipment and polish continuously for 30min-90min. Step 3: After polishing, remove the silicon carbide wafer and ultrasonically vibrate it for 5-20 minutes to remove the abrasive adhering to the silicon carbide wafer, obtaining polished silicon carbide. Then, test the roughness and removal rate after polishing.
Citation Information
Cited By
Preparation method and application of composite abrasive for polishing semiconductor wafer
CN122255946A
